X chromosome cDNA microarray screening identifies a functional PLP2 promoter polymorphism enriched in patients with X-linked mental retardation - Zhang, Lilei; Jie, Chunfa; Obie, Cassandra; Abidi, Fatima; Schwartz, Charles E.; Stevenson, Roger E.; Valle, David; Wang, Tao (Genome Research, 2007)
X-linked Mental Retardation (XLMR) occurs in 1 in 600 males and is highly genetically heterogeneous. We used a novel human X chromosome cDNA microarray (XCA) to survey the expression profile of X-linked genes in lymphoblasts of XLMR males. Genes with altered expression verified by Northern blot and/or quantitative PCR were considered candidates. To validate this approach, we documented the expected changes of expression in samples from a patient with a known X chromosome microdeletion and from patients with multiple copies of the X chromosome. We used our XCA to survey lymphoblast RNA samples from 43 unrelated XLMR males and found 15 genes with significant (≥1.5-fold) reduction in expression in at least one proband. Of these, subsequent analysis confirmed altered expression in 12. We followed up one, PLP2, at Xp11.23, which exhibits approximately fourfold decreased expression in two patients. Sequencing analysis in both patients revealed a promoter variant, −113C>A, that alters the core-binding site of the transcription factor ELK1. We showed that PLP2-(−113C>A) is sufficient to cause reduced expression using a luciferase reporter system and is enriched in a cohort of males with probable XLMR (14 of 239, 5.85%) as compared to normal males (9 of 577, 1.56%) (χ2 = 11.07, P < 0.001). PLP2 is expressed abundantly in the pyramidal cells of hippocampus and granular cells of the cerebellum in the brain. We conclude that our XCA screening is an efficient strategy to identify genes that show significant changes in transcript abundance as candidate genes for XLMR.
10.1101/gr.5336307